Establishment of urban road maintenance model based on performance-based contracts. (3rd April 2023) - Yang, Jyh-Bin; Tseng, Chun-Chieh; Chang, Jia-Ruey; Liu, Chia-Ming
ABSTRACT: Maintaining urban roads in a good condition is a basic duty of any city government. Traditionally, urban road maintenance is performed by a contractor that provides the required manpower and equipment resources to complete the necessary daily inspection and repair works. Although the quality of roads is acceptable, the inefficiency is evident everywhere. A performance-based contract (PBC) is used in the field of road maintenance in various countries, primarily for highway or large-area pavement rehabilitation and follow-up maintenance as the subject of the contract. In this study, we applied the design thinking approach to establish a PBC implementation model for urban road patrolling and sporadic repair. Moreover, to ensure the feasibility of the proposed model and to decrease the political risk of execution outcome, we adopted a two-stage validation in this study. The proposed performance indicators were examined by the historical data of road maintenance in Taipei City, and the feasibility of the proposed PBC implementation model was then confirmed by domain experts. The research outcomes could be used to develop PBCs for maintenance management of other infrastructures with better maintenance performances.